Decohesion of a rigid flat punch from an elastic layer of finite thickness. (June 2020) - Peng, Bo; Feng, Xi-Qiao; Li, Qunyang
Abstract: Interfacial bond strength is a crucial mechanical property of solid adhesive joints that plays an important role in a wide range of applications. A common way of quantifying mechanical strength of an adhered interface is to measure the apparent adhesion strength by finding the maximum pulling force in a tensile bond test and dividing it by the area. Despite the simplicity of this method, there is growing evidence suggesting that the measured quantity is not necessarily an intrinsic attribute of the interface but depends on thickness of the adhesive film and size of the interface. In this work, the critical pull-off force of a flat rigid punch adhered to an elastic film of finite thickness is studied via asymptotic analysis as well as finite element (FE) simulations. The decohesion behavior is found to be governed by two dimensionless parameters η and φ : the former represents the deformation of the interface relative to the interaction distance of interfacial forces, while the latter denotes a correction factor due to finite thickness of the film. As η changes from 0 to infinity, the interface decohesion would take place from uniform detachment ( DMT-like ) to crack-like propagation ( JKR-like ). The transition behavior can be well described by an empirical solution, which suggests a new rational procedure to consistently characterize the intrinsic adhesion properties of an adhered interface from tensile bond tests. Finally, the general empirical solution and the adhesion characterization procedure are directly validated by a series of experiments via detaching a stainless-steel flat punch from adhesive Polydimethylsiloxane (PDMS) films. This work not only offers a clear and explicit solution to capture the transition behavior of interface decohesion but also provides a guideline for modulating adhesion performance via geometry rather than chemistry of the adhesives.